2010
DOI: 10.1007/s10603-010-9127-4
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Gender Differences in Housework Time in Germany

Abstract: Division of housework, Gender, Housework, Time use survey, Structural equation modelling,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…They find that the higher the male's income share, the more time the female spends on doing the chores. Similar findings have been obtained for other countries including Australia (Baxter, 2002), France (Anxo and Carlin, 2004), the UK (van Klaveren et al, 2008) and Germany (Gwozdz and Sousa-Poza, 2010). …”
supporting
confidence: 88%
“…They find that the higher the male's income share, the more time the female spends on doing the chores. Similar findings have been obtained for other countries including Australia (Baxter, 2002), France (Anxo and Carlin, 2004), the UK (van Klaveren et al, 2008) and Germany (Gwozdz and Sousa-Poza, 2010). …”
supporting
confidence: 88%
“…As Hersch and Stratton (2002) argue, the latter result may reflect more severe constraints on the division and timing of housework activities for married individuals that are more likely to interfere with labour market activities. For instance, Alesina et al (2011) show that intra-household bargaining may yield a situation in which married men put more effort on their careers and engage less in household production than single men and 2 For empirical analyses finding a negative impact of wages on hours allocated to housework activities we exemplarily refer to Hersch and Stratton (1994) for the U.S. as well as Gwozdz and Sousa-Poza (2010) for Germany. The latter paper also includes a comprehensive review of the empirical literature on this issue.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…A number of studies have found that gender inequalities exist in time use (Connelly and Kimmel, 2009, Gwozdz and Sousa-Poza, 2010& Burda et al 2013. Ilahi (2000), discussed the composition of male-female time tasks, explained that women work more than men in almost all regions.…”
Section: Introductionmentioning
confidence: 99%